The Palgrave Handbook of Incarceration in Popular Culture
XXXI, 788 p. 24 illus., 23 illus. in color.
Keywords: The Handbook of Incarceration in Popular Culture will be an essential reference point, providing international coverage and thematic richness. The chapters examine the real and imagined spaces of the prison and, perhaps more importantly, dwell in the uncertain space between them. The modern fixation with ‘seeing inside’ prison from the outside has prompted a proliferation of media visions of incarceration, from high-minded and worthy to voyeuristic and unrealistic. In this handbook, the editors bring together a huge breadth of disparate issues including women in prison, the view from ‘inside’, prisons as a source of entertainment, the real worlds of prison, and issues of race and gender. The handbook will inform students and lecturers of media, film, popular culture, gender, and cultural studies, as well as scholars of criminology and justice.